A Systematic Review: Nurses and Digital Health in Community Services - Auliana Tesa; Puteri Dianti; Rika Diah Pitaloka (Universitas Malahayati Lampung, 2026)
ABSTRACT Digital transformation in healthcare has accelerated the use of telemedicine, mobile health (mHealth), and electronic consultation technologies. Nurses, as frontline providers, play a vital role in applying these innovations, especially in community services, home care, and rural areas. However, their specific contributions within digital health ecosystems remain underexplored in systematic reviews. This review aims to identify how nurses implement digital technologies, the professional roles they undertake, and the reported outcomes, barriers, and enabling factors in community and underserved settings. Using the PICo framework and PRISMA 2020 guidelines, literature searches were conducted in ScienceDirect and Wiley Online Library. Inclusion criteria covered English-language empirical studies published between 2019 and 2025. Quality appraisal used the JBI Critical Appraisal Checklist, and thematic synthesis was applied to extract key patterns. Eleven studies met the criteria. Nurses acted as clinical decision-makers, digital health educators, and remote care supervisors. Outcomes included improved service access, communication efficiency, and patient satisfaction. Barriers involved infrastructure gaps, digital literacy, and limited policy support. Enablers included formal training, system interoperability, and organizational leadership. Nurses contribute significantly to digital health implementation in community care. These findings support digital nursing curricula, inclusive policies, and context-driven, sustainable interventions. Keywords: Community Health Centres, Community Health Nursing, Digital Technology, Rural Health, Telemedicine, Systematic Review.